Analisis Efektifitas Penerapan Digital Marketing untuk Membangun Citra Merek dari Mulyosari Group - Jasmine Sabrina Islamy; Virginia Mandasari (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Research on digital marketing is important in doing business in the era of society 5.0. In this study, research was conducted on the analysis of the effectiveness of various kinds of digital marketing that are widely applied by online shop business people who help maximize sales while providing brand image to customers. This research aims to find out which type of digital marketing is the most effective for providing brand image to customers at Mulyosari Group. The research method used is a qualitative approach with data collection conducted through interviews, surveys and observations. The results of the research and testing can show that the most effective digital component used to build a brand image at Mulyosari Group is marketing with social media video content which must maximize the creation of content in the form of videos. Some of the components that are improved are the consistent use of brand identity to the use of call to action in each video The video content created by Mulyosari Group must be able to display and create a brand image for customers and audiences in order to increase sales of each product.